ADDITIONAL NOTES ON THE GENUS PARAGUS LATREILLE (DI PTERA: SYRPHIDAE) FROM PAKISTAN WITH A NEW COUNTRY RECORD - M. A. Hassan; K. Ghorpadé; I. Bodlah; K. Mahmood; Z. Iqbal (Journal of Animal and Plant Sciences, 2018)
Six species of the genus Paragus Latreille,viz. four species under subgenus Pandasyopthalmus and one species each under subgenera Paragus and Serratoparagus are reported from Pakistan. These known species are distributed as follows: Paragus (Paragus) quadrifasciatus Meigen, 1822 and P. (Paragus) compeditus Wiedemann, 1830 from Gilgit- Baltistan; Paragus (Pandasyopthalmus) annandalei Ghorpadé, 1992, P. (Pandasyopthalmus) haemorrhous Meigen, 1822 and P. ( P andasyopthalmus) politus Wiedemann, 1830 from Azad Kashmir and P. ( Serratoparagus) serratus ( Fabricius, 1805) and P. (Pandasyopthalmus) politus Wiedemann, 1830 has been recorded from Punjab province of Pakistan. Paragus (Paragus) quadrifasciatus Meigen, 1822 is a new country record for Pakistan. The six here collected species are mentioned along with their local distributional notes, remarks and diagnostic characters. Photographs of the morphological characters and drawings of male terminalia of all known species have been provided. A checklist of the seven known species of the genus Paragus Latreille is given along with distributional notes. the Indian subcontinent. Claußen and Weipert ( 2004)
Keywords: Paragus; Syrphidae; Pakistan; New Record.